Geochemical and microstructural analysis of paleoproterozoic pseudotachylites in Río de la Plata craton, Tandil belt, Argentina - Frisicale, Maria Cristina (2012)
The current study focuses on the analysis of pseudotachylytes from the Azul Megashear Zone, located in the Río de la Plata craton, central Argentina. This shear zone is a strip of mylonitic rocks of more than 40km in length and with a maximum width of 2.5km. Glassy and microcrystalline pseudotachylytes are hosted by Paleoproterozoic gneiss mylonite, granitoid mylonite, granulite mylonite and striped gneisses. The pseudotachylytes occur as fault and injection veins characterized by sharp contacts with no gradation into the mylonites and show melt- origin features such as partially melted quartz and feldspar clasts with embayed rims and flow structures. Their composition is similar to that of the rocks in which they are injected. In those cases involving banded host rocks, slight chemical differences can be observed in the pseudotachylytes mainly in terms of their fabric and mineralogy. Most pseudotachylytes have textures deriving from post-solidification ductile deformation, but others bearing mylonite-like features are related to viscous flow prior to complete solidification. There are indications that some of these pseudotachylytes were formed during the ductile regime, others being generated in the brittle regime during shear zone reactivation following exhumation or uplift. The occurrence of several pseudotachylyte- generating events indicates intermittent aseismic/seismic slip at different crustal levels throughout this shear zone.